Examining NFU – lessons from Southern Asia. Issue 3 (2nd September 2022) - Sethi, Manpreet
Abstract: The concept of NFU has been around for many decades, but only two of the nine nuclear armed nations have declared NFU doctrines. Both of these China and India, are in Southern Asia, a region that houses three geographically contiguous states with nuclear weapons. Pakistan, the third nuclear armed country in the region, rejects NFU. The paper examines the disparate positions of the three countries in order to find their motivations for and objections against NFU. By understanding their decisions to accept or reject NFU, one can test the strength of the arguments normally made in favour of first use. The paper showcases the utility of NFU as an effective credible strategy that achieves the objective of deterrence at least risk. Such a posture also demands less onerous arsenal requirements, liberates the decision maker from having to lay down redlines on use of nuclear weapons, and eases the ''lose or use'' dilemma of the adversary. Meanwhile, first nuclear use presents itself as not only a dangerous but also non-credible strategy, especially where the adversary has a secure second strike capability. Understanding the benefits of NFU and futility of first use can also help shape global acceptability of NFU as a step towards nuclear disarmament. Till such time as all stakeholders can be convinced of the desirability and feasibility of such a world, acceptance of NFU can be a safe way station.